A Study Of Adherence To Treatment In Patients With Chronic Heart Failure (Texas Journal of Multidisciplinary Studies, 2025)
Adherence to treatment in patients with chronic heart failure was studied. Modern approaches to managing patients with chronic heart failure involve comprehensive drug therapy, symptom control and lifestyle changes. Therefore, the adherence to treat patients with chronic heart failure and study of its characteristics is a crucial issue